Biogeochemical controls on biodegradation of buried oil along a coastal headland beach. (May 2020) - Collins, Autumn Westrick; Elango, Vijaikrishnah; Curtis, David; Rodrigue, Matthew; Pardue, John H.
Abstract: Laboratory experiments investigated oxygen dynamics in buried oiled sands sampled from areas impacted by the Macondo spill. Measured oxygen fluxes in oil deposits that were permeable to tidal water ranged from 10 −3 to 10 −4  μmol/cm 2 -sec, orders of magnitude higher than fluxes in non-permeable deposits (10 −6 to 10 −7  μmol/cm 2 -sec). Oxygen dynamics were well described by 1-d models that represent increased oxygen consumption in oiled sands. Experiments demonstrated that when oxygen is present and the oil deposit is permeable to tidal water, biodegradation of alkylated phenanthrenes and dibenzothiophenes proceeded over time scales (i.e., weeks) to have a significant impact on the mass and quality of buried oil. For this biodegradation process to proceed, two independent conditions must be met, a source of oxygenated water has to be present (e.g., tidal flushing in the intertidal zone) and the oiled deposit has to be permeable to water (i.e., pores cannot be completely saturated with oil). Graphical abstract: Unlabelled Image Highlights: The transport scale of oxygen into oiled sands is mm's via diffusion and cm's via advection. Diffusive flux of oxygen into oil deposits is 3 orders of magnitude lower than advective flux. Laboratory oxygen fluxes explain field observations of weathering in the beach intertidal. PAHs are stable in Macondo oil when oxygen flux is limited in the oil deposit. Maximum losses of PAHs occurred where the nutrient uptake was greatest in the presence of oxygen.